Physical capacity and body composition in 13-16 year old soccer players during three-year training cycle - Konieczna, A.; Radziminski, L.; Paszulewicz, J.; Lopez-Sanchez, G. F.; Dragos, P.; Jastrzebski, Z. (Baltic Journal of Health and Physical Activity, 2019)
The aim of the study was to show changes in aerobic and anaerobic capacity and body composition of the adolescent soccer players in a three-year training cycle. Material and Methods: 16 footballers aged 13 to 16 were examined. Measurements of aerobic fitness were performed with the Cooper and PWC170 tests, and anaerobic fitness with the Wingate test. Body composition measurements were made with an electronic scale. Results: During the three-year training period, significant changes in PWC170 and VO2max were observed depending on the stage of the adolescence and training process. Relative values of anaerobic capacity indicators: total work and maximal power over a three-year period increased significantly (Wt from = 228.2 ±19.2 J/kg to = 263.2 ±19.9 J/kg; Pmax from = 9.19 ±0.86 W/kg to = 10.98 ±0.55 W/kg). Conclusions: Adolescent soccer players have shown significant changes in their exercise capacity and body composition during the three years of the training process. Correlations between selected anaerobic fitness indices and fat free mass were significantly positive.